(untitled) (Research, Society and Development, 2020)
In recent years, studies have been carried out to try to understand the changes in plant development when grown in soils contaminated by diesel oil. The objective of this work was to analyze the initial development of peanuts when grown in soil contaminated by diesel oil. An experiment was carried out in randomized blocks, in a 2x6 factorial scheme, with two peanut cultivars: Top Verde and IAC 503, interacting with five periods of rest after contamination by diesel oil in the soil, namely: contamination in the day (0 day); 30; 60; 90 and 120 days and no oil in the soil (control) and with five repetitions, totaling 60 experimental units. The cultivar IAC 503 stood out in length and dry mass of the aerial part when cultivated in soils contaminated by diesel oil. Diesel oil impairs peanut development even after 120 days after soil contamination. It is recommended to rest above 120 days for growing peanuts in soils contaminated by diesel oil.